A selective and sensitive nanosensor for fluorescent detection of specific IgEs to purified allergens in human serum. Issue 7 (17th January 2018) - Yun, Jianrong; Duan, Fang; Liu, Liming; Chen, Xiulai; Liu, Jia; Luo, Qiuling; Wu, Jing
Abstract : The effective magnetic fluorescence sensing platform was employed to amplify signal and capture target IgE in one step. Abstract : Food allergies are increasingly recognized as a major healthcare concern. In order to sensitively and specifically detect allergies from blood samples of at-risk allergic patients, an effective magnetic fluorescence sensing platform (EMFP) was constructed. The EMFP incorporated hollow mesoporous silica nanospheres (HMNs) to amplify signal from the target IgE in addition to magnetic nanoparticles (MNPs) to capture and separate the target IgE. The application of EMFP to immunoassays indicated a detection limit of 0.0159 ng mL −1 for low concentration specific immunoglobulin E (sIgE) against purified shellfish Metapenaeus ensis (Meta. E.) allergens, which is 15 fold more sensitive than the commercially available Food and Drug Administration-approved analyzers. Notably, EMFP was specific for the targeted sIgE even with interference by other sIgEs. In addition, the detection time is only 75 min, considerably faster than current commercial ELISA kits for IgE assays. Together, these results demonstrated that EMFP has excellent sensitivity and selectivity for the rapid detection of sIgE. The method thus exhibits potential toward the rapid monitoring of sIgE against Meta. E. allergens in clinical application.